PENGARUH LITERASI KEUANGAN DAN PROMOSI TERHADAP MINAT MENGGUNAKAN E-WALLET PADA SANTRIWATI MA PUTERI AL-AMIN MARTAPURA - Lola Malihah; Namiroh Namiroh; Mukhlis Kaspul Anwar (RIBHUNA : Jurnal Keuangan dan Perbankan Syariah, 2024)
In line with rapid technological advancements, the use of smartphones has become an indispensable aspect of modern life. Easy internet access through smartphones has opened up signnificant opportunities for the development of e-commerce. To support online shopping activities, digital wallets have emerged as a popular digital payment innovation. This research aims to identify the influence of financial literacy and promotion on the interest in using e-wallet among female student of MA Puteri Al-Amin Martapura. The study employs a quantitative method conducted through field research reserch. Data collected from a questionnaire distributed to 82 female students using a saturated sampling method serve as primary data. The data analysis reveals that financial literacy does not demonstrate a significant influence on the interest in using e-wallets, with a calculated T-value of -0,651< tabulated T-value of 1,664. However, promotion shows a significant influence on the interest in using e-wallets, with a calculated T-value of 9,988 > the tabulated T-value of 1,664. Based on the F-test , the calculated F-value of 52,144 > the tabulated F-value of 3,111, thus is can be concluded that financial literacy and promotion simultaneously influence the interest in using e-wallets. The R2 result of 56,9% indicates that financial literacy and promotion collectively affect the interest in using e-wallets.